Public Relations Communication Strategies In Improving Regional Image (Study of Lubuklinggau City Regional Government Public Relations) - Solimin, Solimin (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2023)
This research discusses the public relations communication strategy of the Lubuklinggau city government in improving the image of the Lubuklinggau city government. This research aims to find out what communication strategies are used by Lubuklinggau city government public relations in improving the image of Lubuklinggau city government. This research is a qualitative descriptive study with data collection techniques used, namely interviews and observation. The results of the research concluded that Lubuklinggau city government public relations has implemented a public relations strategy, namely exploring the desires of the community, socializing the achievements of the Lubuklinggau city government through the media, managing relationships, developing strategies and developing networks. In accordance with its role, public relations is a tool used to establish good relations between the government, society, mass media and other agencies so that good cooperation occurs. From there, public relations carries out communication activities with the public, media and other agencies. This is done to improve the image within the institution. From these activities and strategies, a harmonious relationship was established between the community and the Lubuklinggau city government. Keywords: Strategy, Communication, Public Relations, Regional Image